The origins of money in the Iron Age Mediterranean world - Heymans, Elon (Cambridge University Press, 2021)
"The introduction of coinage in Ancient Greece is widely regarded as one of the most defining developments to have taken place in antiquity. Invented in Lydia around 630 BCE, it quickly spread across the Greek world and would have a lasting impact on the ancient world. However, other than coinage, money itself was never invented. It emerged and gained critical weight in the Iron Age as a social and economic tool, most dominantly in the form of precious metal bullion. This book is the first study to comprehensively engage with the early history of money in the Iron Age Mediterranean, focusing on both the Levant and the Aegean. Building on a comprehensive study of precious metal hoards, Elon D. Heymans deploys a wide range of sources, both textual and material, to rethink money's role and origins in the history of the eastern Mediterranean."